Nation branding in a globalized competitive world : how can countries utilize nation brands to foster their potential? - Alhassan, Tarik (2023)
This thesis explores how countries can utilize nation brands in a globalized competitive world to foster their potential, and in so doing, how they can achieve the financial benefits referred to in different fields, including attracting tourists and foreign investors. To answer this research question, this study reviews the subject of nation branding, what constitutes a nation’s brand, and what makes a brand a positive one, to then comprehend the significance of effectively communicating the brand globally in order to achieve a positive perception. Qualitative research was conducted within an interpretive epistemology, with the data collected using two methods. The first method was interviews, in which eleven relevant actors from the field were interviewed to discuss various aspects of the topic. This includes what constitutes a positive brand, previous anecdotes with global brands, influential elements in nation branding, and effective brand communications. Interpretative Phenomenological Analysis (IPA) was applied to analyze the data collected in the interviews. Promotional digital campaigns conducted by the study’s chosen nations, the United Arab Emirates and the Kingdom of Spain, were examined through Critical Discourse Analysis (CDA) as a second method in the empirical section. This was to access concrete materials of media actions and comprehend the communication themes and elements used to promote nations and attract foreigners. After analyzing the interviews, the researcher identified themes that define a nation’s brand builders, as well as the importance of both internal and external communications, followed by an analysis of the intersection of politics and nation branding, based on the consensus view of participants. Furthermore, through the reviewed communicated brands’ narrative and elements, CDA enhanced the researcher’s understanding of how nations attempt to impress and attract visitors, investors, and tourists. The findings of the investigation led to the thesis that nation branding is an ongoing and consistent process that is more complicated than what has been described in the literature up to now. The author submits that countries can foster their potential by first developing a competitive brand and then effectively communicating the brand’s narrative and competitive edge using several types of communications channels continuously in order to impress and successfully attract tourists and investors. In the process of branding themselves, nations must sustain a well-built and a competitive brand. Based on the analyzed themes from the interviews with global actors in nation branding, and on the analysis of the campaigns within the theoretical framework, the author identified the brand-building elements that comprise a competitive and attractive nation brand. Vision, policies, the nation’s role and contributions in social, humanitarian, and environmental global issues, infrastructure, culture, history, people, sports, and location are among these elements. Sustaining a competitive brand requires effective and continuous internal and external communications: internally, by informing all stakeholders about the nation’s vision and objectives, and combining its resources to achieve those goals; and externally, by effectively communicating the nation’s narrative, competitive edge, and uniqueness to various global audiences using a variety of communication tools and strategies. The significance of using a variety of communication tools stems from the aim of minimizing any distortion namely from global media platforms mainly due to political or economic motivations. While results from this study indicate that regional political and economic agendas can influence a nation’s brand, nation branding is shown to be ineffective at influencing political agendas.